2018
DOI: 10.1016/j.htct.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cell concentration at cryopreservation on neutrophil engraftment after autologous peripheral blood stem cell transplantation

Abstract: BackgroundPeripheral blood stem cell concentrations are traditionally adjusted to 20–40 × 106 leukocytes/mL prior to freezing. This low cell concentration at cryopreservation implies larger volumes with more dimethyl sulfoxide being used, and higher cost and toxicity at the time of transplant. Higher cell concentrations have been reported but this is not widely accepted. Moreover, the influence of cell concentration on engraftment has not been well documented. Therefore, this study retrospectively analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…One of the main concern related to cryopreservation is represented by the loss of viable cells due to unit processing or during the storage [ 16 , 17 ]. This risk may be exacerbated if products are cryopreserved at cell concentration greater than 2 × 10 8 /ml, or if they contain a large amount of granulocytes [18] , [19] , [20] . In this study, we confirmed that part of viable CD34 + cells was lost with cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main concern related to cryopreservation is represented by the loss of viable cells due to unit processing or during the storage [ 16 , 17 ]. This risk may be exacerbated if products are cryopreserved at cell concentration greater than 2 × 10 8 /ml, or if they contain a large amount of granulocytes [18] , [19] , [20] . In this study, we confirmed that part of viable CD34 + cells was lost with cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Felix et al reported that progressively higher cell concentrations (ranges from less than 2 × 10 8 WBC/mL to greater than 6 × 10 8 WBC/mL) was associated with incrementally longer days to initial ANC recovery in pediatric patients (p values of between‐group comparisons were not reported). Our study of adult patients, in contrast, did not find between group differences in initial ANC recovery, even when the very high NC group (≥5 × 10 8 NC/mL) was compared to the low NC group.…”
Section: Discussionmentioning
confidence: 99%
“…1 In spite of the first report by Rowley, the optimal NC concentration of cryopreserved HPC(A) products has remained controversial as the majority of the recently published literature suggests that this optimal concentration should be less than 3 × 10 8 NC/mL. [2][3][4][5][6][7][8] Administering lower total product volumes with high NC concentrations, however, may have the potential benefit of decreasing volume-and dimethyl sulfoxide (DMSO)-related patient complications, while maximizing the laboratoryʼs liquid nitrogen (LN2) freezer storage capacity. Our study is a retrospective investigation of the effect of HPC(A) products with cell concentrations greater than 3 × 10 8 NC/mL on clinical and product outcomes in patients undergoing autologous PBSC transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these factors, the influence of cell concentration on cryopreservation outcome is not well studied [65]. Two studies have demonstrated that cryopreservation of PBSCs at a concentration of 2 × 10 8 cells/mL still yielded high recovery of viable cells [66] and excellent engraftment after autol­ogous PBSC transplantation [65]. An earlier study even indicated a cell concentration of 3.7 ± 1.9 × 10 8 for cryopreservation of PBSCs did not result in loss of engraftment potential [67].…”
Section: Additional Considerationsmentioning
confidence: 99%